Oxford Handbooks Online 2015
DOI: 10.1093/oxfordhb/9780199337538.013.3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approaches to the Study of Work and Family

Abstract: In an effort to move the field forward work–family scholars continue to evaluate their research with an ever-increasing critical eye. Yet, one area work–family scholars often struggle with is the development and application of theory. Building on previous discussions of theory within the literature, we focus on five theories (i.e., social-exchange theory, person–environment fit theory, adaptation theory, affective events theory, and theory of planned behavior) that have the potential to propel work–family scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…While initially primarily driven by role theory (e.g., Barnett & Hyde, 2001;Champoux, 1980;Greenhaus & Beutell, 1985), over the past several decades work-family research has drawn from a variety of theories, rendering a comprehensive review of theories beyond the scope of this paper. For reviews more focused on theory, interested readers may refer to Greenhaus and ten Brummelhuis (2013), Powell et al (2019), andMatthews et al (2016). For the purposes of the current review, we focus on theories that are playing a prominent role in guiding current work-family research, namely, resource-based theories, work-family boundary management theory, and identity theory.…”
Section: Work-family Theorymentioning
confidence: 99%
“…While initially primarily driven by role theory (e.g., Barnett & Hyde, 2001;Champoux, 1980;Greenhaus & Beutell, 1985), over the past several decades work-family research has drawn from a variety of theories, rendering a comprehensive review of theories beyond the scope of this paper. For reviews more focused on theory, interested readers may refer to Greenhaus and ten Brummelhuis (2013), Powell et al (2019), andMatthews et al (2016). For the purposes of the current review, we focus on theories that are playing a prominent role in guiding current work-family research, namely, resource-based theories, work-family boundary management theory, and identity theory.…”
Section: Work-family Theorymentioning
confidence: 99%
“…Our purpose in discussing theoretical approaches at the outset is to help situate articles from the SLR, and to consider how theoretical approaches to work-family questions have developed over time. 5 For valuable overviews of W-F scholarship, see Allen et al, 2000;Amstad et al, 2011;Bellavia and Frone, 2005;Byron, 2005;Eby et al, 2005;Greenhaus and Parasuraman, 1999;Greenhaus and ten Brummelhuis, 2013;Korabik et al, 2008;Matthews et al, 2015;Perry-Jenkins et al, 2000;and Williams et al, 2016. 6 Although an SLR helps to systematically evaluate a wide range of material, it has limitations by virtue of its methodology (Petticrew and Roberts, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This ongoing neglect is puzzling given the dramatic rise of mobile work, as well as persistent calls by work–family scholars for ‘new theoretical directions’. On this latter point, Matthews et al (2015) and ten Brummelhuis and Bakker (2012) offer valuable new theoretical ideas aimed at revitalizing work–family studies, as does a recent special issue in Academy of Management Review (Powell et al, 2019). Yet, as Williams et al (2016: 520–522) have observed, current theorizing appears to take work–family scholarship in an ‘ever more individualistic direction’, emphasizing issues of individual cognition, decision-making, and positive affect, while neglecting the power relations and macro-structural drivers of work and family life.…”
Section: Examining and Rethinking Work–family Scholarship Through Thementioning
confidence: 99%
See 2 more Smart Citations